Preliminary Analysis of Quantum Dots as a Marking Technique for Ceratitis capitata - Richard Wimbush; Pia Addison; Francois Bekker; Minette Karsten; Melissa Powell; George Marais; Aaisha Moerat; Anandie Bierman; John S. Terblanche (Insects)
This study evaluates the potential of quantum dots (QDs) as a marking method for Mediterranean fruit flies (Ceratitis capitata) (Medfly) in comparison to traditional fluorescent powder. As a highly destructive pest impacting a wide variety of fruit crops, an effective marking technique is essential for improving the biological understanding and management of Medflies, including control strategies like the Sterile Insect Technique (SIT). Through multiple controlled experiments, we examined the effects of QDs and fluorescent powder markers on Medfly flight ability, marker retention rates, and marker durability and stability under diverse storage conditions. Fluorescent powder demonstrated consistently high reliability across all parameters, whereas QDs showed reduced retention, particularly when applied to pupae, and had a more pronounced negative effect on flight ability. This was illustrated by the field trials, which did not recapture any of the QD-marked flies, highlighting the current limitations in QD application methods. Additionally, fluorescent powders outperformed QDs in both long-term storage conditions and short-term stability tests. These findings indicate that while QDs possess potential as marking agents, further refinement of application techniques is required to achieve comparable efficacy to fluorescent powders in pest management contexts.